2013
DOI: 10.1371/journal.pone.0080765
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Hyaluronan and Its Regulators in Pancreatic Ductal Adenocarcinoma

Abstract: BackgroundAlthough pancreatic ductal adenocarcinoma is characterized by an abundant stroma enriched with hyaluronan (HA), the prognostic impact of HA and its regulators remains unknown.MethodsUsing immunohistochemistry, expression patterns of HA and its regulators, including a synthesizing enzyme (HAS2), and a degrading enzyme (HYAL1) were investigated in patients who received surgical resection. The prognostic significance of these markers and other clinicopathological variables was determined using univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
2
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(115 citation statements)
references
References 26 publications
9
97
2
7
Order By: Relevance
“…The fact that HA expression was seen in large tumours more often than in small tumours is consistent with the aforementioned observations as the synthesis of large amounts of ECM is obviously mandatory during tumour progression in PDAC [3,21,22]. The results of our present study are contrast with those of a recent study published by Cheng and colleagues who were able to show a strong correlation between HA expression and patients' overall survival although larger tumours were correlated with higher HA expression in our series [6]. However, different methodologies were used in our study.…”
Section: Discussionsupporting
confidence: 87%
“…The fact that HA expression was seen in large tumours more often than in small tumours is consistent with the aforementioned observations as the synthesis of large amounts of ECM is obviously mandatory during tumour progression in PDAC [3,21,22]. The results of our present study are contrast with those of a recent study published by Cheng and colleagues who were able to show a strong correlation between HA expression and patients' overall survival although larger tumours were correlated with higher HA expression in our series [6]. However, different methodologies were used in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have reported that the excessive accumulation of hyaluronan in cancer tissues is associated with the worse prognosis after surgery in breast [20], gastric [21], and colorectal [22] cancer. In the case of pancreatic adenocarcinoma, the quantitative analysis of the hyaluronan content in resected cancerous tissue revealed that the level was 4–12 times that in normal pancreatic tissues [23,24,25]. This also has a clinical impact on the poor overall survival rate after surgery.…”
Section: Hyaluronan and Its Role In Progression Of Pancreatic Ductmentioning
confidence: 99%
“…41 Indeed, Has2 has been associated with poorer survival in human PDAC. 42 We found Etv1 overexpression was associated with Has2 increase by 4 fold ( Figure 5A). In silico screening demonstrated 3 putative Ets binding sites in the Has2 promoter ( Figure 5B).…”
Section: Etv1 Mediated Stromal Expansion Is Associated With Hyaluronimentioning
confidence: 77%
“…10 High amounts of HA and expression of Has2 in PDAC have been associated with shorter survival after resection, but the molecular mechanisms that lead to increased expression of HA in PDAC have not been elucidated. 42 It has been demonstrated that abundance of HA and other ECM components results in increased interstitial fluid pressure within the tumor that leads to compression of intratumoral blood vessels and represents a barrier to perfusion, diffusion, and convection of chemotherapeutic agents as well as small molecule therapeutics. 10 We have identified Etv1 as a transcriptional activator of Has2 expression, resulting in remarkably increased HA deposition within the PDAC stroma that in turn leads to larger tumors and is accompanied by a more metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%